Reoperations for Bleeding Portal Hypertension. Surgical Rescue of Surgical Failures - Mercado, Miguel Angel (Hindawi Publishing Corporation, 1999)
Background; Surgery for portal hypertension has a low rebleeding rate. Patients that rebleed can be grossly divided into those who die as a consequence of the episode, those who don't die but develop liver failure (remaining as Child-Pugh C) and those who, in spite of the bleeding episode, retain good liver function (Child-Pugh A or B). At our hospital, the latter group is considered for further surgical treatment. We report here the results of surgical rescue of surgical failures. Methods; In a twenty year period, 36 patients (30 Child-Pugh A, 6 Child-Pugh B) were reoperated. The files of these patients were reviewed. Results; Average age was 33 years. Cirrhosis was present in 31 cases. All patients were electively reoperated with portal blood flow preserving procedures. Operative mortality for the whole group was 12% and for the Child-Pugh A group 6.6%. Rebleeding was observed in 5.5%. Postoperative incapacitating encephalopathy was recorded in one case (2.7%). Good quality of life was recorded in 84% of the cases. Survival (Kaplan-Meier) was 78% at 6 months and 69% at 5 years. Conclusions; Surgical failures in low risk patients (Child-Pugh A or B) can be treated by means of surgery, and a low mortality, re-bleeding and encephalopathy rate can be expected. The performance of a portal blood flow preserving procedure is recommended.